The princess bride : S. Morgenstern's classic tale of true love and high adventure - Goldman, William, 1931-2018 (Orlando, Floria : Harcourt Books, Harvest Books, 2007)
A tale of true love and high adventure, pirates, princesses, giants, miracles, fencing, and a frightening assortment of wild beasts.
Introduction to the 30th anniversary edition -- Introduction to the 25th anniversary edition -- The princess bride -- Buttercup's baby: An explanation -- Buttercup's baby, Chapter one: Fezzik dies -- Reading group guide.
Publishers, dates or pagination may vary.
Originally published in 1973.
Keywords: Good and evil -- Fiction; Pirates -- Fiction; Princesses -- Fiction; Castles -- Fiction; Action and adventure fiction; Romance fiction